Chemotherapeutic response of triclabendazole by enzyme-linked immunosorbent assay in experimentally infected sheep witb Fasciola gigantica - Santra, P K; Prasad, A; Ghosh, S (The Indian Journal of Animal Sciences, 2012)
Chemotherapeutic response of triclabendazole (6 mg and 10 mg/kg body weight) was assessed by enzyme-linked immunosorbent assay in 7- month-old sheep experimentally infected with Fasciola gigantica. In infected control group higher antibody response was noticed at 10 weeks PI, whereas, in the treated groups antibody levels declined gradually post-treatment. The results of ELISA were correlated to worm establishment in infected control and treated groups.